2005
DOI: 10.1002/app.22309
|View full text |Cite
|
Sign up to set email alerts
|

Novel stabilization system for polypropylene via the Ziegler–Natta catalyzed polymerization in the presence of aluminum aryloxide

Abstract: ABSTRACT:The aluminum aryloxide was prepared via the reaction of phenolic antioxidant, 3-(3,5-di-t-butyl-4-hydroxyphenyl)-N-octadecylpropionamide, with triethyl aluminum. Propylene polymerization using supported ZieglerNatta catalyst systems was carried out in the presence of the antioxidant or its aluminum aryloxide. Although the antioxidant gave rise to decrease in catalyst yield and change in hydrogen response, the aluminum aryloxide had no influence on the catalytic polymerization behavior, and thus the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…15,16,[24][25][26] In most cases, nucleated PP is used for the applications, which need higher stiffness and heat resistance. The stiffness, heat resistance, and processability of nucleated PP is considered to be a targeted value for nucleated PLA from the viewpoint of evaluating the possibility and applicability as molded articles of the nucleated PLA.…”
Section: Resultsmentioning
confidence: 99%
“…15,16,[24][25][26] In most cases, nucleated PP is used for the applications, which need higher stiffness and heat resistance. The stiffness, heat resistance, and processability of nucleated PP is considered to be a targeted value for nucleated PLA from the viewpoint of evaluating the possibility and applicability as molded articles of the nucleated PLA.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of additives can also disturb monomer recovery process. Because of these technical problems which are not favorable from an industrial point of view, in recent years, few investigations have been reported on the use of antioxidants in the polymerization of propylene, and their effect and chemical structures on the activity of catalyst and properties of the final products. Antioxidants are categorized into primary and secondary classes.…”
Section: Introductionmentioning
confidence: 99%
“…In the phenolic antioxidants, hydroxyl group decreases the catalyst activity through its reaction with catalyst. Therefore, before polymerization, the hydroxyl group needs to react with alkyl aluminum and be converted to aryl oxide groups . Irganox 1330, a phenolic (primary) antioxidant with no ester group in its chemical structure, has a better performance in comparison to those phenolic antioxidants having ester group, because ester groups of antioxidants are capable to interact with the catalyst, and consequently decrease its activity .…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, AOs and additives are mixed with PP by extruder, thereby producing pellets . Pelletizing consumes the huge energy that reported about one‐third of the total energy of PP production .…”
Section: Introductionmentioning
confidence: 99%